A pulmonary hypertension-producing plant from Tanzania. Issue 4 (August 1975) - Heath, D; Shaba, J; Williams, A; Smith, P; Kombe, A
Abstract : An African youth who had died from primary pulmonary hypertension was suspected of having ingested a herbal remedy containing the seeds of the local plant Crotalaria laburnoides. Consequently powdered seeds of this plant were fed to 20 Wistar albino rats for 60 dyas to see if this would induce ventricular hypertrophy and associated hypertensive pulmonary vascular disease. At the end of the experimental period right ventricular hypertrophy, medial hypertrophy of the pulmonary trunk and 'muscular pulmonary arteries', and muscularization of the pulmonary arterioles had developed in a proportion of the test animals. These are the morbid anatomical features pathognomonic of a raised pulmonary arterial pressure and show that the seeds of Crotalaria laburnoides contain an agent capable of inducing pulmonary hypertension in rats. This study suggests the value of seeking a history of ingestion of herbal remedies and drugs in cases of unexplained pulmonary hypertension in man.